Literature Review of QR-Code-Based Transparency Democracy Learning Design of Pancasila and Civics Education - Kandiri; Aransyah, Ade; Nurwahidin, Muhammad; Kusuma, Febra Anjar; Prakasa, Nugraha Medica (UNDIKMA, 2025)
This research aims to design QR Code-based digital media that can be used in learning Pancasila and Citizenship Education. This media is expected to increase student participation in the election of the head of the organization, as well as provide easy access to information related to the election. By using QR codes, students can easily access relevant information, thus increasing transparency in the election process. This research shows that the application of QR Code-based digital media in learning Pancasila and Citizenship Education not only increases transparency in the election of the head of the organization, but also contributes to the development of students' critical thinking skills. By utilizing information technology, it is expected that the election process can be carried out in a more accountable and transparent manner, in line with the principles of democracy expected by Indonesian society.